Target price accuracy: South African equity market - Sebele, Potso (My University, 2019)
Much that has been studied around target prices has generally revealed weak prediction ability on individual analysts’ level. In this report, we pursue an unprecedented approach and analyse consensus target price forecasting ability. Like past academic works, we conclude that, consensus target price accuracy in forecasting future market share price is inadequate, with consistent prediction errors that are fairly auto-correlated. We also discovered that target price prediction errors are correlated to earnings forecast errors suggesting that the latter is underpinned by earnings forecast. Regarding our last objective, we found out that prediction errors are positively related to implicit return, earnings per share and price per book value but negatively related to market capitalisation of companies.
Master of Management in Finance and Investments, June 2019
Keywords: Johannesburg Stock Exchange; Stocks--Prices--South Africa; Investment analysis--South Africa